2014
DOI: 10.1111/jnc.12729
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of N‐myc downstream‐regulated gene 2 attenuates reactive astrogliosis and inflammatory response in a mouse model of cortical stab injury

Abstract: N-myc downstream-regulated gene 2 (Ndrg2) is a differentiation-and stress-associated molecule predominantly expressed in astrocytes in the CNS. In this study, we examined the expression and the role of Ndrg2 after cortical stab injury. We observed that Ndrg2 expression was elevated in astrocytes surrounding the wounded area as early as day 1 after injury in wild-type mice. Deletion of Ndrg2 resulted in lower induction of reactive astroglial and microglial markers in the injured cortex. Histological analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 48 publications
2
37
0
Order By: Relevance
“…NDRG3 and NDRG4, on the other hand, are strongly expressed in neurons [10], and Ndrg4-deficient mice show impairments of spatial learning and neuroprotection because of a decrease in the level of BDNF [15]. Although Ndrg2-deficient mice have been reported to attenuate neuronal damage after brain injury [16], no structural or functional abnormalities in the brains of Ndrg2-deficient mice have been identified. Because mediators of cellular stress responses, such as hypoxia-inducible factor 1α (HIF-1α) [17,18] and reactive oxygen species (ROS) [19] up-regulate NDRG2 expression, NDRG2 may contribute to the modulation of stress-induced physiological and pathological processes within the nervous system.…”
Section: Introductionmentioning
confidence: 97%
“…NDRG3 and NDRG4, on the other hand, are strongly expressed in neurons [10], and Ndrg4-deficient mice show impairments of spatial learning and neuroprotection because of a decrease in the level of BDNF [15]. Although Ndrg2-deficient mice have been reported to attenuate neuronal damage after brain injury [16], no structural or functional abnormalities in the brains of Ndrg2-deficient mice have been identified. Because mediators of cellular stress responses, such as hypoxia-inducible factor 1α (HIF-1α) [17,18] and reactive oxygen species (ROS) [19] up-regulate NDRG2 expression, NDRG2 may contribute to the modulation of stress-induced physiological and pathological processes within the nervous system.…”
Section: Introductionmentioning
confidence: 97%
“…However, in a cortical stabbing injury model in mice, both GFAP and NDRG2 were elevated, and NDRG2 showed a stress responsiveness that was related to the early astroglial activation, reactive astrogliosis, and the subsequent inflammatory response, at least in part, via the activation of IL-6/STAT3 inflammatory signaling [41]. Overall, these NDRG2 may regulate astroglial activation through the suppression of cell proliferation and the stabilization of cell morphology.…”
Section: Physiological Functions Of Ndrg2 In the Nervous Systemmentioning
confidence: 99%
“…[ 41] findings demonstrated that NDRG2 is an early-stage stress-responsive gene and is correlated with astroglial activation and the subsequent inflammatory reaction. Whether the NDRG2-mediated cell stress response is an endogenous neural protection mechanism or is involved in pathological injury remains to be elucidated.…”
Section: Physiological Functions Of Ndrg2 In the Nervous Systemmentioning
confidence: 99%
“…The method we used to make a stab wound injury model was modified based on previous studies. [47][48][49] Mice were anesthetized by intraperitoneal injection of 4% chloral hydrate (1 mL/100 g). We use a needle diameter of 0.7 mm and the injury point was 2 mm left of themed line and 2.5 mm underneath the lambdoid suture (Fig.…”
Section: Animal Modelmentioning
confidence: 99%